Social capital and migration: A case study of rural Vietnam - Đào Vũ Phương Linh; Nguyễn Thị Thùy Dung; Lê Mỹ Kim (My University, 2019)
Social capital and migration: A case study of rural Vietnam
Keywords: Social capital; Migration; Rural Vietnam